A comprehension of the Burr type-II distribution based on records: Properties, estimation and prediction (Journal of Statistical Research, 2026)
This article introduces the Burr Type-II distribution and derives various point estimates for unknown parameters based on record statistics. It also presents predictions for future record values from a Bayesian perspective, supported by a numerical study to illustrate the results. Furthermore, the article covers the properties of the Burr Type-II distribution and includes the calculation of entropy and extropy functions, as well as an investigation of stochastic orders such as usual stochastic order, likelihood ratio order, and hazard rate order.Journal of Statistical Research 2025, Vol. 59, No. 2, pp. 325-342